Correlation of scopoletin-induced fluorescence with visible PPD symptoms in greenhouse cassava - Nor Hasima, Mahmod; Beeching, John (2017)
Post-harvest physiological deterioration (PPD) is spoilage of cassava storage roots characterized by browning of parenchyma tissue and vascular streaking. A striking feature of PPD is an accumulation of hydroxycoumarins, such as scopoletin, scopolin, esculetin and esculin, which are products of phenylpropanoid pathway. PPD, which renders the roots unpalatable and unmarketable, leads to significant yield loss in global cassava production. Extensive studies have been conducted to understand the biochemical activities and pathways involved in PPD in which the result requires an evaluation of PPD symptoms which is usually based on a visual scoring system. However, high variations are consistently observed between biological replicates making analysis difficult. Therefore, there is urgent need to find a reliable marker since the generation of reliable data that can be shared or compared between institutions is desirable. The use of scopoletin-induced fluorescence as a PPD marker was tested in greenhouse-grown cassava storage roots by comparing fluorescence measurements and the PPD scores generated from normal light photographs of the harvested roots. It was found that all freshly harvested root samples lacked fluorescent but after 24 hours they dramatically fluoresced to a high level. However, the occurrence of intense fluorescence was not accompanied by intense PPD symptoms as fluorescence level declined when visible PPD symptoms developed. Hence, the use of fluorescence or scopoletin as an alternative marker for PPD remain unconvincing, mainly because it did not parallel with PPD symptom accumulation observed.